DEFINITIONS, ISSUES AND CHALLENGES OF DIGITAL LIBRARIES - Mishra, Rakesh Kumar (Innovare Journal of Education, 2016)
Abstract: Â Digital library is nothing but the transformation from traditional library. Digital libraries concept come into existence in 21st century. Virtual library, electronic library, library without walls & digital library are synonymous to each other. In this paper we have to discuss about the definition of digital library, its challenges and issues, advantages, disadvantages etc. Using digital library anyone can access anything, anytime, anyform to provide right information to right user at right time. Keywords: Digital Collection, Technology, SDL,FDL,HDL, Myths